Warm-up, stretching, and cool-down strategies for combat sports - Costa, P. B.; Medeiros, H. B.; Fukuda, D. M. S. (Strength and Conditioning Journal, 2011)
Combatants have been fighting for thousands of years. Structured combat sports between 2 men have existed for hundreds of years as a sport similar to what we currently know as mixed martial arts (mma). Several changes have occurred in mma in the last 2 decades, allowing the sport to become more professional, with rules, media exposure, agents, and millions of spectators worldwide. Thus, it is important today for athletes and strength and conditioning coaches to become familiar with the most appropriate forms of training for these modalities, including not only fighting technique but also other related components of optimal physical conditioning, such as warm-up, flexibility training, and cool-down.